El derecho común en la obra de Lope de Vega: unos breves apuntamientos (2005)
This article refers to the main manifestations Lope de Vega has with respect to the Common Law in some of his comedies in which he mentioned some famous lawyers, styles, and practices developed in the complex Spanish juridical world of Modern Age which inherited many bajomedievales elements.